Long COVID Syndrome: A Comprehensive Review of Multisystem Sequelae and Clinical Management Strategies - Gaurav, Vinay; Yadav, Jyoti; Kumari, Savita (Journal of Neonatal Surgery, 2025)
Long COVID, also known as Post-Acute Sequelae of SARS-CoV-2 Infection (PASC), is briefly talked about in this piece, along with how to treat it and the part that many systems play. It has an effect on the lungs, heart, brain, and muscular system. New studies and suggestions from the World Health Organization and the Centers for Disease Control and Prevention (CDC) have helped us understand how it works, what the main symptoms are, and how to treat it. Patients who have recovered from acute COVID-19 often still feel tired, short of breath, have trouble thinking, and have mental health problems weeks or months later. Healthcare professionals face a big task when helping people recover from long COVID. They need to take a comprehensive approach.